Global Validation of the AO Spine Upper Cervical Injury Classification. Issue 22 (15th November 2022) - Vaccaro, Alexander R.; Lambrechts, Mark J.; Karamian, Brian A.; Canseco, Jose A.; Oner, Cumhur; Benneker, Lorin M.; Bransford, Richard; Kandziora, Frank; Shanmuganathan, Rajasekaran; El-Sharkawi, Mohammad; Kanna, Rishi; Joaquim, Andrei; et al.
Abstract : Study Design: Global cross-sectional survey. Objective: To determine the classification accuracy, interobserver reliability, and intraobserver reproducibility of the AO Spine Upper Cervical Injury Classification System based on an international group of AO Spine members. Summary of Background Data: Previous upper cervical spine injury classifications have primarily been descriptive without incorporating a hierarchical injury progression within the classification system. Further, upper cervical spine injury classifications have focused on distinct anatomical segments within the upper cervical spine. The AO Spine Upper Cervical Injury Classification System incorporates all injuries of the upper cervical spine into a single classification system focused on a hierarchical progression from isolated bony injuries (type A) to fracture dislocations (type C). Methods: A total of 275 AO Spine members participated in a validation aimed at classifying 25 upper cervical spine injuries through computed tomography scans according to the AO Spine Upper Cervical Classification System. The validation occurred on two separate occasions, three weeks apart. Descriptive statistics for percent agreement with the gold-standard were calculated and the Pearson χ 2 test evaluated significance between validation groups. Kappa coefficients (κ) determined the interobserver reliability and intraobserver reproducibility. Results: The accuracy of AO Spine members to appropriately classify upper cervical spine injuries was 79.7% on assessment 1 (AS1) and 78.7% on assessment 2 (AS2). The overall intraobserver reproducibility was substantial (κ=0.70), while the overall interobserver reliability for AS1 and AS2 was substantial (κ=0.63 and κ=0.61, respectively). Injury location had higher interobserver reliability (AS1: κ = 0.85 and AS2: κ=0.83) than the injury type (AS1: κ=0.59 and AS2: 0.57) on both assessments. Conclusion: The global validation of the AO Spine Upper Cervical Injury Classification System demonstrated substantial interobserver agreement and intraobserver reproducibility. These results support the universal applicability of the AO Spine Upper Cervical Injury Classification System. Level of Evidence: 4